The interplay between event and background sedimentation and the origin of fossil-rich carbonate concretions: a case study in Permian rocks of the Paraná Basin, Brazil - Bondioli, João Guedes; Matos, Suzana Alves; Warren, Lucas Verissimo [UNESP]; Assine, Mário Luis [UNESP]; Riccomini, Cláudio; Simões, Marcello Guimarães [UNESP] (Scandinavian University Press, 2015)
The Permian Serra Alta Formation was generated under transgressive conditionswithin a large, calm epeiric sea. A monotonous succession of ‘barren’, massive mud-stones deposited under oxygen-deﬁcient conditions (mainly below storm wave base)is the main lithofacies of this unit. Fossils are generally rare and diluted in the matrix,but certain intervals contain shell-rich concentrations with well-preserved, closedarticulated bivalves, mixed with shells and comminuted debris with variable quality ofpreservation, all encased in carbonate concretions. Two main scenarios may accountfor the origin of these bivalve-rich concretions (i.e. unique events in sea-water chemis-try or unique burial-starvation couplets). Sedimentological and taphonomic informa-tion indicates that the ﬁnal deposition of the original shell-rich mudstone intervalswas probably tied to episodic inﬂux of ﬁne-grained sediments in distal settings. Mod-erate bioturbation is also recorded suggesting low rates of sedimentation prior to earlydiagenesis. Hence, the fossil concentrations in concretions were formed due to theinterplay of event and background sedimentation. These are internally simple concen-trations with complex depositional histories. The concretion-bearing beds are not ran-domly distributed in the Serra Alta Formation. Rather, they are found in the sparselyfossiliferous offshore deposits of the basal to intermediate portions of the unit. Thus,the concretionary mudstone beds and associated deposits are preserved in particularintervals and can be tracked for kilometres. This indicates that the conditions essentialfor concretion development existed only at particular stratigraphical intervals. Finally,our study strongly corroborates the idea that concretions are critical sources of sedi-mentological, taphonomic and stratigraphical information.
Keywords: Biostratinomy; Bivalves; Carbonate concretions; Fossil diagenesis; Permian